Issues of Gay Community on the Novel of Simon VS the Homo Sapiens Agenda - Dewi Wijaya; Irpan Ali Rahman (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2021)
The study aims to know how social community on gayâ€™s life through the novel of Simon vs the Homo sapiens agenda written by Becky Albertalli. The title of this research is â€œ The Analysis of Main Character on Confessions of A Shopaholic Novel through Freudian Theory written by Sophie Kinsellaâ€. Confessions of A Shopaholic novel is tells about a women named Rebecca Bloomwood who has bad behavior that are shopping addiction to fulfill her desire but she gets anxiety because of her debts and it disturbs her psychological. This research will focuses on Rebeccaâ€™s anxiety.The data are taken from the novel in the form of dialog and monolog. The writer using psychoanalysis theory from Sigmund Freud that related with anxiety theory. Sigmund Freud theory has 3 kinds of anxiety, there are realistic anxiety, neurotic anxiety and moral anxiety. This theory is used to analyze the cause and effect of Rebecca Bloomwoodâ€™s anxiety.Last, the writer found the proved from Rebecca experiences three kinds of anxiety. First is neurotic anxiety caused by her mom character and it might be related to Rebecca childhood, Rebecca canâ€™t to be honest to her mom about the cost of her skirt or clothes, she always tells if they are cheap because she knows her mom will shocked and angry if she now the truth, that can related if Rebecca canâ€™t fulfill her desire when she was child because of her mom character. Second is realistic anxiety caused by her bad habit in shopping, that makes Rebecca has a lot of debts and that makes she becomes panic everytime met her debt collector. And the last moral anxiety caused by she felt guilty of her shopping behavior. And she becomes a liar to defense herself